2021
DOI: 10.2196/25771
|View full text |Cite
|
Sign up to set email alerts
|

User Experience With Dynamic Difficulty Adjustment Methods for an Affective Exergame: Comparative Laboratory-Based Study

Abstract: Background In affective exergames, game difficulty is dynamically adjusted to match the user’s physical and psychological state. Such an adjustment is commonly made based on a combination of performance measures (eg, in-game scores) and physiological measurements, which provide insight into the player’s psychological state. However, although many prototypes of affective games have been presented and many studies have shown that physiological measurements allow more accurate classification of the pl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 47 publications
(113 reference statements)
0
3
0
Order By: Relevance
“…Recent studies have begun exploring hybrid approaches that combine performance and affective data to refine DDA [24,29]. This integration aims to address the limitations of relying solely on one type of data, marking a promising direction for future research and application in the field.…”
Section: Related Workmentioning
confidence: 99%
“…Recent studies have begun exploring hybrid approaches that combine performance and affective data to refine DDA [24,29]. This integration aims to address the limitations of relying solely on one type of data, marking a promising direction for future research and application in the field.…”
Section: Related Workmentioning
confidence: 99%
“…Optimal game performance requires a balance between a player's ability and task difficulty. 19,20 found that children with ADHD prefer activities for the process rather than the outcome. This insight guided our puzzle design, emphasizing user involvement and visual appeal while simplifying spelling challenges to enhance engagement and attention.…”
Section: Balance Between Ability and Task Difficultymentioning
confidence: 99%
“…Optimal game performance requires a balance between a player's ability and task difficulty 19,20 . found that children with ADHD prefer activities for the process rather than the outcome.…”
Section: Game Designmentioning
confidence: 99%